Local Strongmen At The Village Level: The Conflict Of The Demolition Of The First Raja Brawijaya ‘Petilasan’ At Sudimoro Village, Jombang - Mirojul Huda; Novy Setia Yunas (LPPM Universitas PGRI Sumatera Barat, 2017)
Having been enacted since 2014, the Act No. 6/2014 has given a spirit and a huge authority to the villages in developing their potential resources. Unfortunately, those special authorities have not been fcollowed by the leadership’s capacity of the village’s head. This paper attempts to analyze the rise of local actors so-called local strongmen at the village level. This study uses Sidel (1999) perspective on how to seek local strongmen in local area at Sudimoro Village, Megaluh District in Jombang Regency. In case, the head of Sudimoro village produces a despotic action by unloading and dredging the historical land where there was a petilasan from King of Majapahit, well-known as Raja Brawijaya 1. Then, this action eventually triggered a conflict in the middle of its society and has been solved after the hall of cultural heritage of the government of Jombang Regency has intervened. This paper concluded that the high of authority and power would potentially rise the new local strongmen at the village level. Therefore, the existence of the principle of recognition and subsidiarity owned by the village is only used by a few local elites for their interests without any accountability and accessibility for the society.